Comparative analysis of European bat lyssavirus 1 pathogenicity in the mouse model. - Elisa Eggerbauer; Florian Pfaff; Stefan Finke; Dirk Höper; Martin Beer; Thomas C Mettenleiter; Tobias Nolden; Jens-Peter Teifke; Thomas Müller; Conrad M Freuling (Public Library of Science (PLoS), 2017)
European bat lyssavirus 1 is responsible for most bat rabies cases in Europe. Although EBLV-1 isolates display a high degree of sequence identity, different sublineages exist. In individual isolates various insertions and deletions have been identified, with unknown impact on viral replication and pathogenicity. In order to assess whether different genetic features of EBLV-1 isolates correlate with phenotypic changes, different EBLV-1 variants were compared for pathogenicity in the mouse model. Groups of three mice were infected intracranially (i.c.) with 102 TCID50/ml and groups of six mice were infected intramuscularly (i.m.) with 105 TCID50/ml and 102 TCID50/ml as well as intranasally (i.n.) with 102 TCID50/ml. Significant differences in survival following i.m. inoculation with low doses as well as i.n. inoculation were observed. Also, striking variations in incubation periods following i.c. inoculation and i.m. inoculation with high doses were seen. Hereby, the clinical picture differed between general symptoms, spasms and aggressiveness depending on the inoculation route. Immunohistochemistry of mouse brains showed that the virus distribution in the brain depended on the inoculation route. In conclusion, different EBLV-1 isolates differ in pathogenicity indicating variation which is not reflected in studies of single isolates.